2012
DOI: 10.1111/j.1540-8191.2011.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Early- and Long-Term Survival in Patients Undergoing Extracorporeal Membrane Oxygenation (ECMO)

Abstract: Early ECMO application before catastrophic clinical deterioration and weaning as soon as possible may enhance overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…Studies of longer term outcomes after VA ECMO (ranging from 1 year to 10 years) have shown overall survival rates ranging from 17% to 40% [2,4,[6][7][8][9]19]. To date, few of these studies have investigated the outcomes of the subgroup of patients who has been successfully weaned from ECMO and if factors present at ECMO initiation influence long-term survival.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies of longer term outcomes after VA ECMO (ranging from 1 year to 10 years) have shown overall survival rates ranging from 17% to 40% [2,4,[6][7][8][9]19]. To date, few of these studies have investigated the outcomes of the subgroup of patients who has been successfully weaned from ECMO and if factors present at ECMO initiation influence long-term survival.…”
Section: Introductionmentioning
confidence: 96%
“…Refractory cardiogenic shock and circulatory failure are conditions, which carry mortality rates in excess of 70% despite aggressive treatments [1][2][3][4][5][6][7][8][9]. Venoarterial (VA) extracorporeal membrane oxygenation (ECMO) has emerged as a useful rescue therapy for the temporary stabilization of such patients allowing more definitive treatment or recovery from the acute disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Bu cihazların kullanımı ve hasta için uygunluğu, kliniğin deneyimine, hastanın klinik özelliklerine, yaşı ve ağırlığına göre değişebilmek-tedir. [1][2][3][4][5][6][7] Mekanik yardımcı kalp cihazlarından biri olan ECMO, solunum sistemine ya da dolaşım sistemine, beden dışı geçici yapay bir destek sağlayarak, hastanın kalp ve akciğerini günlerce ve haftalarca destekleyerek hastanın iyileşmesine yardımcı olmaktadır. ECMO hem kardiyak hem de solunum desteği sağlayan kısa süreli destek cihazları arasında yer almaktadır.…”
Section: Ekstrakorporeal Membran Oksijenasyonunclassified
“…VV ECMO, kardiyak pompa desteği sağlayamamasına karşın, sağ ventrikül fonksiyonlarını düzelterek, hipoksiyi gidermesi ve sağ ventrikülün daha az hacim ile çalışmasına katkıda bulunmasıyla gerekli hemodinamik ve pulmoner desteği sağlamak amacıyla kullanılmaktadır. 3,9,10,17,18 VV ECMO için iki ayrı kanül kullanılarak boyunfemoral bölge ya da sağ-sol femoral bölge seçimi yapılabileceği gibi, çift lümenli kanül ile sağ internal juguler ven kanülasyonu da yapılabilir. Her iki durumda da dolaşıma dikkat edilmelidir (Şekil 4).…”
Section: Ecmo Veno-arteriyel (Va) Ve Veno-venöz (Vv) Olarak Kullanılaunclassified
“…4 Many of these patients will never return home because of the disability of postintensive care syndrome associated with prolonged intensive care unit care. 4 With respect to patients who have received VA-ECMO, previous observational studies have provided data on traditional short-term survival outcomes, [5][6][7] but at present there is still a paucity of information on these important long-term health-related quality of life outcomes. It is clear that our future outcome trials also must focus on health-related quality of life, perhaps as the primary end point, rather than mortality.…”
mentioning
confidence: 99%